Effects of decarbonization on the energy system and related employment effects in South Africa. Issue 124 (October 2021) - Hanto, Jonathan; Krawielicki, Lukas; Krumm, Alexandra; Moskalenko, Nikita; Löffler, Konstantin; Hauenstein, Christian; Oei, Pao-Yu
Highlights: Coal currently dominates the energy mix in South Africa. South Africa can achieve a power sector relying on 100% renewable energy by 2045. The decarbonization is mainly driven by wind power and photovoltaics. Provinces will benefit from new employment opportunities related to renewable energy. A just energy transition without net job losses only brings negligible cost increases. Abstract: This paper assesses the impact of decarbonization on the energy system and related employment in South Africa. The cost-minimizing, global energy system model (GENeSYS-MOD) is utilized to project two energy mix scenarios and their associated employment implications at provincial level. While the business as usual (BAU) scenario shows a continuous use of coal capacity in the South African power sector until 2050, the 2 °C scenario exhibits a phase-out of coal by 2040 and a higher diversification of power generation dominated by solar and wind capacity. The increase in renewable energy sources (RES) generates employment in the energy sector which can partially substitute the decline in coal related jobs in affected regions. However, it is not certain that the employment created by RES will directly benefit those negatively impacted by the transition. The results of a sensitivity of the 2 °C scenario provide a near cost-optimal energy system in line with a just transition towards a 2 °C world that limits the employment impacts for former coal regions. Thus, a technological transition from a coal- to a RES-based system needs comprehensive plans for job-transfers, policy formulations, support mechanisms and structural transformation.